Transient liquid-phase conductive adhesive containing high-entropy low-melting-point alloy filler as well as preparation and application of transient liquid-phase conductive adhesive
By using high-entropy, low-melting point alloy particles as metal fillers in Ag-based conductive glue, the problem of both dendrites forming and performance in harsh environments is solved, and the conductivity, thermal conductivity, electrochemical migration resistance and mechanical properties are significantly improved.
Patent Information
- Application Number
- CN202510270886.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-06-10
AI Technical Summary
The existing Ag-based conductive glues are prone to form dendrites in harsh environments, resulting in short-circuit failure, and it is difficult to take into account both conductivity, thermal conductivity, electrochemical migration resistance and mechanical properties.
High-entropy low-melting point alloy particles are used as metal fillers. By designing high-entropy alloy particles with specific components in conductive glue, the mixed entropy effect and phase interface complexity of the alloy system are increased, dendrites are inhibited, and the resistance to electrochemical migration is improved.
It significantly improves the conductivity, thermal conductivity, electrochemical migration resistance and mechanical properties of conductive adhesives, reduces preparation costs and environmental risks, and improves the comprehensive performance and long-term use stability of the material.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrically conductive adhesives, and particularly to a transient liquid-phase electrically conductive adhesive containing high-entropy low-melting-point alloy fillers and its preparation and application. Background Art
[0002] The development of electronic packaging material technology is one of the core driving forces for the iterative innovation of electronic product technology. Among them, electrically conductive adhesives (ECAs), as a key electronic packaging material, play an important role in the fields of electronic packaging and chip manufacturing due to their advantages such as low interconnect temperature, simple process, strong compatibility, and environmental friendliness. Ag-based electrically conductive adhesives can provide efficient conductive and heat transfer paths through the three-dimensional conductive network formed by fillers in the polymer matrix, but there are still problems such as insufficient electrical conductivity and mechanical properties. In addition, Ag-based electrically conductive adhesives are more susceptible to reliability problems such as electrochemical migration (ECM) under harsh service environments such as high temperature, high pressure, and high humidity. Therefore, it is urgent to modify Ag-based electrically conductive adhesives in an economical and efficient manner to achieve low-temperature connection, excellent comprehensive performance, stable long-term use, and effectively inhibit ECM to meet the actual needs in the field of power electronics.
[0003] Based on this, the present invention is proposed. Summary of the Invention
[0004] By adding different types of conductive fillers, the performance of electrically conductive adhesives can be significantly improved. Factors such as the morphology, size, and type of fillers all have important effects on the electrical conductivity and mechanical properties of electrically conductive adhesives. Transient Liquid Phase Electrically Conductive Adhesive (TL) is a new type of electrically conductive adhesive material. It introduces low melting point alloy particles into Ag-based electrically conductive adhesives. Utilizing the liquid phase formed by their melting during the curing process, a diffusion reaction occurs with high melting point silver flake powder (Ag flakes) at the solid-liquid interface, generating intermetallic compounds with higher melting points, thereby significantly enhancing the comprehensive performance of the electrically conductive adhesive. Among them, the transient liquid phase usually refers to the combination of "high melting point - low melting point" materials, achieving material interconnection through the solid-liquid interdiffusion mechanism. The ratio of high and low melting point metal components at the interconnection interface will continuously change and is accompanied by a phase change. The low melting point component usually exists in the liquid phase during the process and will be mostly converted into high melting point intermetallic compounds after isothermal solidification and will no longer melt and coat. The low melting point alloy particles used in this technology usually refer to metals, alloys, or their derivatives with a melting point below 250 °C, such as binary alloys tin-bismuth (Sn58Bi), gallium-indium (GaIn), ternary alloys gallium-indium-tin (GaInSn), bismuth-tin-indium ternary alloy (BiInSn), tin-silver-copper (SnAgCu), etc. However, the existing alloy systems have limited room for improving the performance of electrically conductive adhesives. The electrically conductive adhesives are prone to forming dendrites in harsh environments, leading to short circuit failure, and it is difficult to simultaneously consider electrical conductivity, thermal conductivity, resistance to electrochemical migration, and mechanical properties.
[0005] To partially solve the above technical problems, the present invention provides a transient liquid phase electrically conductive adhesive containing high entropy low melting point alloy fillers, as well as its preparation and application. By designing high entropy alloy particles with specific compositions as metal fillers for electrically conductive adhesives, the mixing entropy effect and phase interface complexity of the alloy system are increased, the formation of dendrites is inhibited, and the resistance of the electrically conductive adhesive to electrochemical migration is improved.
[0006] Specifically, in the first aspect, the present invention provides a metal filler for electrically conductive adhesives, including high entropy low melting point alloy particles, and the alloy components of the high entropy low melting point alloy particles are tin-indium-gallium-zinc alloy, bismuth-indium-gallium-zinc alloy, or tin-bismuth-gallium-zinc alloy; The composition of the tin-indium-gallium-zinc alloy is: 18 - 22 wt.% tin, 20 - 28 wt.% indium, 30 - 35 wt.% gallium, and the balance is zinc The composition of the bismuth-indium-gallium-zinc alloy is: 22 - 27 wt.% bismuth, 23 - 28 wt.% indium, 18 - 24 wt.% gallium, and the balance is zinc; The composition of the tin-bismuth-gallium-zinc alloy is: 17 - 23 wt.% tin, 18 - 24 wt.% bismuth, 28 - 33 wt.% gallium, and the balance is zinc.
[0007] In the present invention, by using the high-entropy low-melting-point alloy particles of the above specific components as the metal filler for the conductive adhesive, the mixing entropy effect and the phase interface complexity of the alloy system are increased, the formation of dendrites is inhibited, and the anti-electrochemical migration ability of the conductive adhesive is improved. In the present invention, the introduction of the high-entropy low-melting-point alloy particles can form a uniform and stable conductive network in the silver-based conductive adhesive, significantly improving the electrical conductivity, thermal conductivity, and anti-electrochemical migration ability of the material, and effectively reducing the preparation cost and environmental risk.
[0008] According to the metal filler for the conductive adhesive provided by the present invention, the particle size of the high-entropy low-melting-point alloy particles is 0.5 - 5 μm; Research has found that the high-entropy low-melting-point alloy particles are well-matched in size with silver flakes. That is, when the high-entropy low-melting-point alloy particles are within the controllable range (0.5 - 5 μm), the small particles can fully fill the small gaps between the silver flakes, complete the melting and diffusion reaction to form a better three-dimensional conductive network, and form a good metallurgical bond with the adhesive substrate material, thereby improving the electrical and mechanical properties of the conductive adhesive simultaneously.
[0009] The morphology of the high-entropy low-melting-point alloy particles is spherical or elliptical, which is convenient for further controlling the particle size and the uniformity of the particle size distribution, and is preferably 1 - 5 μm.
[0010] Further controlling the size of the alloy particles within 2 - 4 μm can more significantly improve the anti-electrochemical migration performance, thermal conductivity, and damp heat stability of the conductive adhesive.
[0011] Specifically, the high-entropy low-melting-point alloy particles with appropriate sizes in the present invention as the metal filler for the conductive adhesive bring about multi-faceted performance improvements to the transient liquid-phase conductive silver adhesive. First, the smaller particle size increases the contact area between the particles, forms a denser conductive path, and at the same time reduces the interface resistance, which is beneficial to the improvement of the electrical conductivity. Second, the uniformly distributed small particles reduce the stress concentration, which is beneficial to the improvement of the mechanical properties of the conductive silver adhesive. In terms of process performance, the small particles improve the fluidity, facilitate the filling of microvoids, and improve the coating uniformity.
[0012] Secondly, the present invention also provides a preparation method for the metal filler for the conductive adhesive as described above, including: In an inert atmosphere, according to the mass percentages of the metal elements in the high-entropy low-melting-point alloy particles, each metal raw material is heated and melted to obtain a molten state and mixed to obtain a first mixture. The first mixture, a first dispersant, and a solvent are mixed, and then ultrasonic cavitation treatment is carried out. After cooling, solid-liquid separation is performed, and the solid-phase component is collected to obtain the high-entropy low-melting-point alloy particles.
[0013] According to the preparation method of the metal filler for conductive adhesive provided by the present invention, the ultrasonic frequency of the ultrasonic cavitation treatment is 10-120 kHz, the ultrasonic power is 50-300 W, and the ultrasonic time is 60-120 min.
[0014] By regulating the dosage ratio of alloy components and ultrasonic parameters and other conditions, the present invention realizes the precise regulation of the particle size of the low-melting-point alloy, successfully controls its size within 0.5-5 μm, and through verification, the metal filler obtained by mixing the prepared high-entropy low-melting-point alloy particles with silver flake powder can significantly improve the anti-electrochemical migration performance, thermal conductivity and damp-heat stability of the conductive adhesive.
[0015] Preferably, the ultrasonic frequency is 10-40 kHz, the ultrasonic power is 50-120 W, and the ultrasonic time is 90-120 min.
[0016] Through verification, under the above parameters for ultrasonic cavitation treatment, the obtained high-entropy low-melting-point alloy particles have smaller particle size and more uniform particle size distribution, and have a higher improvement degree on the anti-electrochemical migration performance, thermal conductivity and damp-heat stability of the conductive adhesive.
[0017] According to the preparation method of the metal filler for conductive adhesive provided by the present invention, the first dispersant is selected from polyvinylpyrrolidone; and / or, the solvent is selected from ethylene glycol.
[0018] Preferably, the mass-volume ratio of the metal raw material to the solvent is 0.5-0.65 g: 30-40 mL; Preferably, the proportion of the first dispersant in the solvent is 0.1-0.2 mol / L.
[0019] It is found through experiments that using the above solvent in the present invention is beneficial to controlling the morphology of the alloy particles to be spherical or elliptical; the combined use of the above solvent and the first dispersant and controlling their dosages within the range defined by the present invention is more beneficial to obtaining more spherical alloy particles, and thus is beneficial to controlling the size of the alloy particles.
[0020] In a third aspect, the present invention also provides a silver-based transient liquid-phase conductive adhesive, comprising: a first metal filler and a second metal filler; The first metal filler is selected from silver flake powder; The second metal filler is selected from the metal filler for conductive adhesive as described above; The mass ratio of the first metal filler to the second metal filler is greater than 8:2.
[0021] According to the silver-based transient liquid-phase conductive adhesive provided by the present invention, the particle size of the silver flake powder is 4-6 μm.
[0022] The silver-based transient liquid-phase conductive adhesive provided by the present invention, by weight, comprises: 5-6 parts of a first metal filler, 0.2-0.4 parts of a second metal filler, 1-2 parts of a polymer matrix, 0.5-1 part of a coupling agent, 1.5-2.5 parts of a second dispersant, 1.5-2.5 parts of a reducing agent, and 0.5-1 part of a curing agent; Preferably, the polymer matrix is selected from epoxy resins; Preferably, the coupling agent is selected from γ-aminopropyltriethoxysilane; Preferably, the second dispersant is selected from ethanol; Preferably, the reducing agent is selected from carboxylic acids; Preferably, the curing agent is selected from polyetheramines.
[0023] Fourthly, the present invention also provides a preparation method of the silver-based transient liquid-phase conductive adhesive as described above, comprising: Adding the first metal filler and the coupling agent into the second dispersant, stirring and ultrasonically dispersing to prepare solution A; Adding the second metal filler and the reducing agent into the second dispersant, ultrasonically dispersing to prepare solution B; Mixing solution A and solution B, stirring and ultrasonically treating for 20-40 min to obtain a mixed solution; Heating the polymer matrix, maintaining at 50-70 °C for 4-6 min, adding the mixed solution, continuously stirring for 50-70 min, and adding the curing agent to obtain a paste-like conductive adhesive with viscosity.
[0024] The paste-like conductive adhesive of the present invention is preheated at 70-90 °C for 15-25 min, and then cured at 110-130 °C, and the general curing time is 40-60 min.
[0025] When adding the mixed solution, it can be slowly added after the polymer matrix reduces its viscosity, such as at a rate of 100 ml / min.
[0026] It has been verified that for the preparation method of the conductive adhesive, with each parameter within the above range, combined with the selection of the type of raw materials and their ratio, the obtained conductive adhesive has more excellent comprehensive properties, especially the resistance to electrochemical migration and the damp heat stability.
[0027] Fifthly, the present invention also provides an application of the silver-based transient liquid-phase conductive adhesive as described above in automotive electronics, power electronics or aerospace.
[0028] The present invention provides a transient liquid-phase conductive adhesive containing a high-entropy low-melting-point alloy filler, and its preparation and application. By designing high-entropy alloy particles with specific compositions as metal fillers for the conductive adhesive, the mixing entropy effect and phase interface complexity of the alloy system are increased, the formation of dendrites is inhibited, and the anti-electrochemical migration ability of the conductive adhesive is improved.
[0029] Furthermore, the present invention prepares small-sized low-melting-point alloy particles with a uniform particle size distribution, and mixes them with silver flake powder as the metal filler of the conductive adhesive. The low-melting-point alloy particles have a particle size of 0.5-5 μm and a uniform particle size distribution. Combined with the raw material selection, dosage ratio, and preparation process in the conductive adhesive, it can significantly improve the anti-electrochemical migration ability of the conductive adhesive; it can significantly reduce the thermal resistance and improve the thermal conductivity of the conductive adhesive; it can reduce the contact resistance drift during the long-term use of the conductive adhesive and improve the aging resistance of the conductive adhesive; it can significantly improve the stability of the conductive adhesive under high temperature and high humidity; and it has the advantage of low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the following drawings are some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0031] Figure 1 Among them, (a), (b), and (c) are SEM images of the high-entropy low-melting-point alloy particles obtained in Example 2, Example 4, and Example 5 of the present invention, respectively.
[0032] Figure 2 It is a schematic diagram of the in-situ WDT observation test platform in the anti-electrochemical migration performance test of Test Example 4 of the present invention. Among them, (a) is the electrochemical migration test, (b) is the schematic diagram of dendrite growth, (c) is the self-built on-site water droplet test observation platform, and (d) is the actual test sample electrode.
[0033] Figure 3 It is the light microscope images of the conductive adhesives obtained in Example 8 and Example 9 of the present invention and the control product Ag-ECA. Among them, (a) is Ag-ECA, (b) is 10TLP-ECA, and (c) is 20TLP-ECA.
[0034] Figure 4 It is the I-t curve (a) in the ECM test of the conductive adhesives obtained in Example 7-9 of the present invention and the control product Ag-ECA.
[0035] Figure 5 It is the average short-circuit failure time (b) in the ECM test of the conductive adhesives obtained in Example 7-9 of the present invention and the control product Ag-ECA.
[0036] Figure 6 are the densities after curing of the electrically conductive adhesives obtained in Examples 7 - 9 of the present invention and the control sample Ag - ECA.
[0037] Figure 7 are the changes of the thermal diffusivity (a) and the thermal conductivity of the electrically conductive adhesives obtained in Examples 7 - 9 of the present invention and the control sample Ag - ECA with the test temperature after curing (b).
[0038] Figure 8 are the changes of the resistivity of the electrically conductive adhesives obtained in Examples 7 - 10 of the present invention and the control sample Ag - ECA with the aging time at 85°C (a) and the changes of the shear force with the aging time at 120°C (b).
[0039] Figure 9 are the changes of the resistivity of the electrically conductive adhesives obtained in Examples 7 - 10 of the present invention and the control sample Ag - ECA with the aging time at 85°C / 85% RH (a) and the changes of the shear force with the aging time (b). Detailed Embodiments
[0040] All other embodiments obtained by those of ordinary skill in the art based on the embodiments in the present invention without creative efforts fall within the scope of protection of the present invention.
[0041] In the embodiments, the information of each raw material is shown in the following table.
[0042] The environmental pressure described in the present invention refers to the standard atmospheric pressure, the value of which is 101,325 Pascals (Pa), and it can also be expressed as 1.01325 bars (bar) or 760 millimeters of mercury (mmHg).
[0043] For those not specified with specific techniques or conditions in the embodiments, they are carried out according to the techniques or conditions described in the literature in the field or according to the product specifications. For the reagents or instruments not specified with the manufacturer, they are all conventional products that can be obtained through commercial purchase.
[0044] The present invention will be described below with reference to specific embodiments. It should be noted that these embodiments are only descriptive and do not limit the present invention in any way.
[0045] Example 1 This example provides a method for preparing high - entropy low - melting - point alloy particles, and the specific steps are as follows: (1) Weigh metal raw materials according to mass percentages, which contain 20% Sn, 26% In, 33% Ga, and 21% Zn, place them in a vacuum induction furnace, introduce argon for protection, and melt and mix them to obtain a molten first mixture.
[0046] (2) Add 0.2 g of the molten first mixture in step (1) to a solution of polyvinyl pyrrolidone (PVP) and ethylene glycol (EG), wherein the concentration of polyvinyl pyrrolidone in the solution is 0.15 mol / L, and the mass-volume ratio of the first mixture to the solution is 0.58 g:35 mL. Stir and disperse, and then perform ultrasonic cavitation treatment at 80 °C, with a frequency of 40 kHz, a power of 120 W, and a time of 60 min; after cooling, centrifuging, and washing, high-entropy low-melting-point alloy particles are obtained.
[0047] The present invention realizes precise control of the size of high-entropy low-melting-point alloy particles by regulating process conditions such as the type of solvent and ultrasonic cavitation parameters (such as ultrasonic power, frequency, and time).
[0048] Example 2 This example provides a method for preparing high-entropy low-melting-point alloy particles, which is basically the same as Example 1, except that the ultrasonic cavitation treatment time is 90 min.
[0049] Example 3 This example provides a method for preparing high-entropy low-melting-point alloy particles, which is basically the same as Example 1, except that the ultrasonic cavitation treatment time is 120 min.
[0050] Example 4 This example provides a method for preparing high-entropy low-melting-point alloy particles, which is basically the same as Example 1, except that the ultrasonic frequency is 40 kHz, the ultrasonic power is 240 W, and the ultrasonic time is 90 min.
[0051] Example 5 This example provides a method for preparing high-entropy low-melting-point alloy particles, which is basically the same as Example 1, except that the ultrasonic frequency is 80 kHz, the ultrasonic power is 240 W, and the ultrasonic time is 90 min.
[0052] Example 6 This example provides a method for preparing high-entropy low-melting-point alloy particles, which is basically the same as Example 1, except that the ultrasonic frequency is 80 kHz, the ultrasonic power is 120 W, and the ultrasonic time is 120 min.
[0053] Comparative Example 1 This comparative example provides a method for preparing high-entropy low-melting-point alloy particles, which is basically the same as Example 1, except that the ultrasonic cavitation treatment time is 5 min.
[0054] Comparative Example 2 This comparative example provides a method for preparing high-entropy low-melting-point alloy particles, which is basically the same as that of Example 1, except that the ultrasonic cavitation treatment time is 10 min.
[0055] Comparative Example 3 This comparative example provides a method for preparing high-entropy low-melting-point alloy particles, which is basically the same as that of Example 1, except that the ultrasonic cavitation treatment time is 30 min.
[0056] Test Example 1 Influence of Different Ultrasonic Cavitation Times on the Size of Alloy Particles Test Object: High-entropy low-melting-point alloy particles obtained in Examples 1 to 6 and Comparative Examples 1 to 3.
[0057] Test Method: First, SEM image acquisition was carried out, and based on the SEM images (SEM images of the alloy particles obtained in Examples 2, 4, and 5 are as Figure 1 shown, and the others are not shown), the particle size was measured multiple times using image post-processing software (Image J) to obtain the particle size range, average particle size, and variance of the alloy particles.
[0058] Test Results: The particle sizes of the alloy particles obtained at different ultrasonic cavitation times are shown in Table 1.
[0059] Table 1
[0060] Combined Figure 1 with Table 1, it can be seen that the diameter ranges of the high-entropy low-melting-point alloy particles prepared at 40 kHz / 120 W and 40 kHz / 240 W are 1 - 10 μm and 0.5 - 19 μm, respectively. However, the diameter range of the high-entropy low-melting-point alloy particles synthesized at 80 kHz / 240 W is 0.4 - 9 μm. Therefore, as the frequency increases, the particle size further decreases ( Figure 1 b and c in). The increase in power has little effect on the overall average particle size of the particles, but it will make the particle size range larger. Among them, when the ultrasonic time is 90 - 120 min, the alloy particles have a smaller particle size and a more uniform distribution.
[0061] The high-entropy low-melting-point alloy particles obtained in Examples 1 to 6 of the present invention can be used as metal fillers for silver-based transient liquid-phase conductive adhesives, and the application process is described in detail below.
[0062] Example 7 This example provides a silver-based transient liquid-phase conductive adhesive, the raw materials of which include: silver flake powder, ethanol, KH550, carboxylic acid, E44 epoxy resin, polyetheramine, and the high-entropy low-melting-point alloy particles obtained in Example 3.
[0063] Among them, the mass-volume ratio of silver flake powder to ethanol is 5.5 g:5 ml; The mass ratio of silver flake powder to KH550 is 5.5:0.7; The mass volume ratio of silver flake powder and carboxylic acid is 5.5g:2ml; The mass ratio of silver flake powder to E44 epoxy resin is 5.5g:1.3g; The mass ratio of silver flake powder to polyetheramine is 5.5g:0.7g; The mass ratio of the silver flake powder to the high entropy low melting point alloy particles obtained in Example 3 is 95:5.
[0064] This embodiment also provides a method for preparing the transient liquid phase conductive adhesive, comprising: (1) Add silver flake powder and KH-550 into ethanol, stir and disperse by ultrasonic to obtain solution A; (2) adding high entropy low melting point alloy particles and carboxylic acid into ethanol and ultrasonically dispersing them to obtain solution B; (3) Solutions A and B were mixed by magnetic stirring and ultrasonically dispersed for 30 minutes to obtain an ethanol solution of Ag-high entropy low melting point alloy particles. E44 epoxy resin was kept at 60°C for 5 minutes to reduce its viscosity. E44 epoxy resin was slowly added to the obtained ethanol solution of Ag-high entropy low melting point alloy particles at a rate of 100 ml / min, and the curing agent was added after continuous stirring for 60 minutes to finally obtain a paste-like conductive adhesive; (4) The paste-like conductive adhesive was preheated at 80°C for 20 min and then cured at 120°C for 50 min to obtain a silver-based transient liquid phase conductive adhesive, which was recorded as 5TLP-ECA.
[0065] Example 8 This embodiment provides a silver-based transient liquid phase conductive adhesive, which is basically the same as Example 7, except that the mass ratio of the silver flake powder to the high-entropy low-melting-point alloy particles obtained in Example 3 is 90:10, recorded as 10TLP-ECA.
[0066] Example 9 This embodiment provides a silver-based transient liquid phase conductive adhesive, which is basically the same as Example 7, except that the mass ratio of the silver flake powder to the high entropy low melting point alloy particles obtained in Example 3 is 80:20, recorded as 20TLP-ECA.
[0067] Example 10 This embodiment provides a silver-based transient liquid phase conductive adhesive, which is basically the same as Example 7, except that the mass ratio of the silver flake powder to the high-entropy low-melting point alloy particles obtained in Example 3 is 85:15, recorded as 15TLP-ECA.
[0068] Conductive adhesive samples with different contents of high entropy and low melting point alloy particles were prepared in Examples 7 to 10 of the present invention. In order to comprehensively evaluate the electrical, mechanical, thermal and other core performance indicators of TLP~ECA conductive adhesives with size-controllable high entropy and low melting point alloy particles, the following tests were performed.
[0069] Test Example 2 Electrochemical Migration Resistance Test Test object: the conductive adhesive obtained in Examples 7 to 9.
[0070] Test method: In order to study the anti-electrochemical migration performance of Ag-ECA and TLP-ECA, the water drop test (WDT) was carried out on the ECA electrode at room temperature according to GB / T 35494.1-2017. Figure 2 Figure 1 is a schematic diagram of the in-situ WDT observation test platform. During the WDT process, a digital source meter is used to apply bias and measure the current between the two electrodes with a resolution of 0.1 fA.
[0071] According to the American Printed Circuit Association Electrochemical Migration Test Standard (IPC-TM-650 Method 2.6.14.1), deionized water was dripped between the two electrodes using a pipette, and a bias voltage was applied to the two electrodes through a probe. At the same time, the entire WDT process was recorded in situ using an ultra-depth of field microscope. Combined with the current-time data recorded by the computer test software (It curve), the mean time to failure (TTF) was determined based on the time of the first current surge and the dendrite bridging observed by the optical microscope. The TTF caused by ECM can be defined as the time required for a short circuit to occur. To check the repeatability, all ECM measurements were repeated at least six times.
[0072] The conductive adhesive (Ag-ECA) prepared by adding only silver flake powder as metal filler was used as a control.
[0073] Test results: ECM in-situ process light microscope picture as follows Figure 3 As shown in the figure, ac are Ag-ECA, 10TLP-ECA and 20TLP-ECA electrodes respectively; the It curves in the ECM test and the average short-circuit failure times of different samples are shown in the figure. Figures 4 - 5 shown.
[0074] from Figure 3 It can be seen that under the 3V bias condition, a small amount of bubbles appeared near the cathode of Ag-ECA in the initial stage, which was because hydrogen was generated at the cathode. As time went on, the color of the anode and cathode edges of the Ag-ECA electrode gradually deepened, corrosion near the anode became more and more serious, and more dendrites began to form at the cathode. After 57s, the cathode dendrites of the Ag-ECA electrode grew to the anode, so the ECM short-circuit failure time of the Ag-ECA electrode under 3V bias was 57s.
[0075] Depend on Figure 3 As shown in b, the 10TLP-ECA electrode began to dissolve near the anode after 50 seconds. After 100 seconds, small dendrites appeared at the cathode. After 182.5 seconds, the dendrites reached the anode and formed a bridge. The short-circuit failure time was 182.5 seconds, which was about 3.2 times that of the Ag-ECA electrode.
[0076] Depend on Figure 3 From the c in Fig. 2, it can be seen that after 100s, several obvious dendrite products appeared on the cathode of the 20TLP-ECA electrode. After 372.3s, the dendrite products reached the anode and formed a bridge. The short-circuit failure time was 372.3s, which was about 2.1 times that of the 10TLP-ECA electrode and 6.5 times that of the Ag-ECA electrode. The above results prove that TLP-ECA with high entropy and low melting point alloy particles is significantly better than traditional Ag-ECA in terms of anti-electrochemical migration performance.
[0077] Figures 4 - 5 It curves obtained when Ag-ECA and TLP-ECA were subjected to ECM tests at different voltages are shown. The short-circuit failure time of Ag-ECA under a bias voltage of 3V is 57s. After adding 5wt.% and 10wt.% high-entropy low-melting-point alloy particles, the short-circuit failure time of the TLP-ECA sample gradually prolonged, and failed at 145s and 182.5s, respectively. The maximum short-circuit failure time of 20TLP-ECA is 372.3s, which is 6.5 times that of Ag-ECA. Therefore, it can be concluded that the addition of small-sized high-entropy low-melting-point alloy particles further improves the anti-electrochemical migration performance of Ag-ECA.
[0078] Test Example 3 Thermal Conductivity Test As the interconnect material of power devices, conductive adhesive will involve thermal conductivity in practical application. The thermal performance of TLP-ECA needs to dissipate the heat generated by the chip in time. The thermal conductivity is tested as follows.
[0079] Test object: the conductive adhesive obtained in Examples 7 to 9.
[0080] Test method: Sample preparation: The size of the thermal conductivity test sample is 10×10mm and the thickness is 2mm. Therefore, a certain amount of conductive glue is placed in a stainless steel mold (a stainless steel mold with a groove of 10mm×10mm×8mm), and then cured layer by layer at 70℃, and the conductive glue is properly compacted with a stainless steel cube. When the height of the conductive glue in the mold is about 6mm, a pressure of 2MPa is applied, and then cured at 130℃ for 60min. After cooling to room temperature, a cube-shaped cured sample of conductive glue with metallic luster is obtained. The sample is taken out of the mold, and the surface of the sample is polished with 400~5000 mesh sandpaper. The sample is ground into a cubic sample with a side length of 10mm and a thickness of about 2mm, ensuring that the upper and lower surfaces of the sample are parallel, smooth and clean.
[0081] Test and result processing: The density of the cured sample was tested according to ISO 16525-1; the thermal diffusion coefficient of the sample was measured by laser flash method according to ISO 22007-4, and the specific heat capacity of the sample was measured by differential scanning calorimeter; the flash temperature points were selected as 30°C, 150°C, and 250°C in the test, and the heating rate was 5°C / min. Then, the thermal conductivity (ie, thermal conductivity) λ of the conductive adhesive was calculated by the formula shown in formula (1). Formula (1) is as follows: λ = α × ρ × c (1) In the formula is the thermal conductivity (W / m·K), is the thermal diffusion coefficient (mm 2 / s), is the sample density (g / cm 3 ), c is the specific heat capacity of the sample (J / g·K). Finally, the thermal conductivity (i.e. thermal conductivity) of TLP-ECA was calculated by formula (1).
[0082] In the test, a conductive adhesive (Ag-ECA) prepared by adding only silver flake powder as a metal filler was used as a control.
[0083] Test results: Figure 6 The density of the samples after TLP-ECA solidification changes with the content of high entropy and low melting point alloy particles; Figure 7 (a) shows the variation trend of thermal diffusion coefficient of conductive adhesive samples with different small-size high-entropy low-melting-point alloy particle contents at different test temperatures after curing; Figure 7 (b) in the figure is the thermal conductivity of the conductive adhesive samples with different small-size high-entropy and low-melting-point alloy particle contents at different test temperatures after curing. The thermal conductivity of the conductive adhesive samples with different high-entropy and low-melting-point alloy particle contents in the range of 30 ℃~300 ℃ after curing is shown in Table 2.
[0084] Depend on Figure 6It can be seen that the overall density trend of the samples after solidification of high entropy and low melting point alloy particles with different contents is the same. The densities of Ag-ECA, 5TLP-ECA, 10TLP-ECA and 20TLP-ECA after solidification are 3.25g / cm 3 、3.28g / cm 3 、3.43g / cm 3 and 3.45g / cm 3 .
[0085] Table 2
[0086] Depend on Figure 7 It can be seen that the thermal diffusion coefficient of TLP-ECA conductive adhesive increases with the increase of high entropy low melting point alloy particle content. The thermal diffusion coefficient of 10TLP-ECA is higher than that of other conductive adhesives. At 30~200℃, the thermal diffusion coefficient of each sample increases with the increase of test temperature.
[0087] As can be seen from Table 2, the thermal diffusion coefficients of Ag-ECA, 5TLP-ECA, 10TLP-ECA and 20TLP-ECA at 200°C are 6.85 mm 2 / s、7.01mm 2 / s、7.64mm 2 / s、6.92mm 2 / s.
[0088] like Figure 7As shown in the figure, within the range of 30~200℃, the thermal conductivity of each sample increases with the increase of the test temperature. However, when the test temperature exceeds 200℃, the thermal conductivity of all samples drops significantly within the range of 200~300℃. This shows that the thermal conductivity of each sample after curing is mainly affected by the internal microstructure of the sample. With the increase of the test temperature, the epoxy resin further shrinks and solidifies, more metallurgical bridges are formed between the internal conductive fillers, the density of the microstructure is improved, and a good thermal conductive channel is formed. However, after exceeding 200℃, the overall thermal conductivity decreases due to the decomposition of the epoxy resin. The maximum thermal conductivity of the cured samples of Ag-ECA, 5TLP-ECA, 10TLP-ECA and 20TLP-ECA at 30℃~300℃ were 9.39W / m·K, 10.10W / m·K, 12.17W / m·K and 10.37W / m·K, respectively. The thermal conductivity of TLP-ECA is better than that of Ag-ECA, indicating that the addition of small-sized high-entropy low-melting alloy particles improves the thermal conductivity of Ag-ECA. This may be due to the fact that during the curing process, the high-entropy low-melting alloy particles fully melt and react completely with Agflakes, which helps to improve the thermal conductivity of the conductive adhesive. For example, at a test temperature of 200℃, the thermal conductivity of the 10TLP-ECA sample is 1.3 times that of the Ag-ECA sample.
[0089] Test Example 4 Thermal stability and wet heat stability performance test Conductive adhesives have disadvantages such as unstable electrical and thermal conductivity and low bonding strength after long-term use. The present invention tests the volume resistivity and shear strength changes of TLP-ECA under thermal aging and wet heat aging conditions through high temperature aging (85°C, 1000h) and high temperature and high humidity (85°C / 85%RH, 1000h) tests, thereby evaluating its performance stability and reliability under long-term service conditions.
[0090] Test object: the conductive adhesive obtained in Examples 7 to 9.
[0091] Test method: According to the JESD22-A101 standard, the conductive adhesive is tested for heat aging at 85℃ and 120℃, and for damp heat aging at 85℃ / 85% RH. The main purpose is to measure the changes in the resistivity and shear strength of the conductive adhesive with aging time.
[0092] Test results: The thermal aging test results are as follows: Figure 8 As shown in the figure, (a) shows the change of resistivity of Ag-ECA and TLP-ECA samples with high temperature aging time; (b) shows the change of shear strength of different ECA samples with aging time at 120℃. Figure 9As shown, where (a) is the variation trend of the volume resistivity of ECA with different addition amounts of high-entropy low-melting-point alloy particles with aging time under the aging conditions of 85°C / 85%RH, and (b) is the shear strength of conductive adhesives with different contents of high-entropy low-melting-point alloy particles at 85°C / 85%RH.
[0093] As can be seen from Figure 8 (a) in, at 85°C, the resistivity change trends of Ag-ECA and TLP-ECA are the same. Both show a phenomenon that the resistivity first decreases and then levels off. After 150h of high-temperature aging, the resistivities of Ag-ECA, 5TLP-ECA, 10TLP-ECA, and 20TLP-ECA decrease by 35.26%, 11.74%, 2.96%, and 30.44% respectively. After 150h to 1000h, the resistivity of the conductive adhesive levels off. The resistivity changes of TLP-ECAs with small-sized high-entropy low-melting-point alloy particles are small and stable during the high-temperature aging test. However, when the addition amount is high, the resistivity change is large.
[0094] As can be seen from Figure 8 (b) in, the shear strength of the conductive adhesive decreases with the increase of aging time. After aging at 120°C for 1000h, the shear strengths of Ag-ECA, 5TLP-ECA, 10TLP-ECA, 15TLP-ECA, and 20TLP-ECA decrease to 5.56MPa, 6.99MPa, 7.54MPa, 7.72MPa, and 8.74MPa respectively. The results show that the mechanical and electrical reliabilities of the conductive adhesives with high-entropy low-melting-point alloy particles are better than those of Ag-ECA.
[0095] As can be seen from Figure 9 (a) in, for the Ag-ECA sample at the beginning of aging (50h), the resistivity shows a downward trend. As the aging time prolongs, the resistivity of the sample gradually increases. For the conductive adhesive with small-sized high-entropy low-melting-point alloy particles (TLP-ECA), during the aging process at 85°C / 85%RH, the resistivity change trend is the same as that of Ag-ECA. Due to its relatively low resistivity itself, the resistivity increment during the test is also small. After aging for 1000h, the resistivities of Ag-ECA, 5TLP-ECA, 10TLP-ECA, and 20TLP-ECA increase to 12.95×10 -4 Ω·cm, 5.85×10 -4 Ω·cm, 5.27×10 -4 Ω·cm, and 8.68×10 -4 Ω·cm respectively. The results show that TLP-ECA with high-entropy low-melting-point alloy particles added has higher electrical reliability, and the test results all meet the JESD22-A101 standard.
[0096] from Figure 9 As can be seen from (b), for ECA with different contents of high-entropy low-melting-point alloy particles, after aging for 1000 h, the shear strength of ECA decreased by 53.1%, 48.9%, 46.2% and 65.8%, respectively. The results show that 5TLP-ECA and 10TLP-ECA have better mechanical stability at 85℃ / 85%RH, and their performance is better than that of traditional Ag-ECA.
[0097] Combination Figure 8 and Figure 9 It can be seen that the transient liquid phase Ag-based conductive adhesive provided in the present invention with small-sized high-entropy low-melting alloy particles added has better performance than traditional silver-based conductive adhesive in high-temperature aging test and high-temperature and high-humidity test.
[0098] The above results confirm that the size-controllable high-entropy low-melting alloy particles provided by the present invention with transient liquid phase conductive adhesive have the performance characteristics of low-temperature curing and good thermal conductivity. At the same time, TLP-ECA has good long-term reliability such as good wet heat stability and resistance to electrochemical migration.
[0099] In summary, the present invention has developed a new Ag-based conductive adhesive material suitable for automotive electronics, power electronics, aerospace and other fields: a transient liquid phase conductive adhesive containing a high-entropy low-melting-point alloy filler. Compared with traditional Ag-based conductive adhesive materials, this material has good electrical, mechanical and thermal properties while taking into account controllable preparation costs, and shows excellent improvement effects in key properties such as anti-aging, moisture and heat resistance, and resistance to electrochemical migration.
[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A metal filler for conductive adhesive, characterized in that: It comprises high entropy low melting point alloy particles, wherein the alloy components of the high entropy low melting point alloy particles are tin-indium-gallium-zinc alloy, bismuth-indium-gallium-zinc alloy or tin-bismuth-gallium-zinc alloy; The composition of the tin-indium-gallium-zinc alloy is: 18-22wt.% tin, 20-28wt.% indium, 30-35wt.% gallium and the balance zinc The composition of the bismuth, indium, gallium and zinc alloy is: 22-27wt.% bismuth, 23-28wt.% indium, 18-24wt.% gallium and the balance zinc; The composition of the tin-bismuth-gallium-zinc alloy is: 17-23wt.% tin, 18-24wt.% bismuth, 28-33wt.% gallium and the balance zinc.
2. The metal filler for conductive adhesive according to claim 1, characterized in that: The particle size of the high entropy low melting point alloy particles is 0.5-5 μm; Preferably, the particle size of the high-entropy low-melting-point alloy particles is 2-4 μm.
3. The method for preparing the metal filler for conductive adhesive according to claim 1 or 2, characterized in that: include: In an inert atmosphere, the metal raw materials are heated and melted to obtain a molten state and mixed to obtain a first mixture according to the mass percentage of each metal element in the high-entropy low-melting-point alloy particles. The first mixture, a first dispersant and a solvent are mixed, and then ultrasonic cavitation treatment is performed, and then cooling, solid-liquid separation and solid phase components are collected to obtain the high-entropy low-melting-point alloy particles.
4. The method for preparing the metal filler for conductive adhesive according to claim 3, characterized in that: The ultrasonic frequency of the ultrasonic cavitation treatment is 10-120kHz, the ultrasonic power is 50-300W, and the ultrasonic time is 60-120min; Preferably, the ultrasonic frequency is 10-40 kHz, the ultrasonic power is 50-120 W, and the ultrasonic time is 90-120 min.
5. The method for preparing the metal filler for conductive adhesive according to claim 3 or 4, characterized in that: The first dispersant is selected from polyvinyl pyrrolidone; and / or, the solvent is selected from ethylene glycol; Preferably, the mass volume ratio of the metal raw material to the solvent is 0.5-0.65 g:30-40 mL; Preferably, the first dispersant accounts for 0.1-0.2 mol / L in the solvent.
6. A silver-based transient liquid phase conductive adhesive, characterized in that: The raw materials include: a first metal filler and a second metal filler; The first metal filler is selected from silver flake powder; The second metal filler is selected from the metal filler for conductive adhesive according to claim 1 or 2 or the metal filler for conductive adhesive prepared by the preparation method according to any one of claims 3 to 5; The mass ratio of the first metal filler to the second metal filler is greater than 8:
2.
7. The silver-based transient liquid phase conductive adhesive according to claim 6, characterized in that: The particle size of the silver flake powder is 4-6 μm.
8. A silver-based transient liquid phase conductive adhesive according to claim 6 or 7, characterized in that: In parts by weight, it includes: 5-6 parts of a first metal filler, 0.2-0.4 parts of a second metal filler, 1-2 parts of a polymer matrix, 0.5-1 parts of a coupling agent, 1.5-2.5 parts of a second dispersant, 1.5-2.5 parts of a reducing agent, and 0.5-1 parts of a curing agent; Preferably, the polymer matrix is selected from epoxy resins; Preferably, the coupling agent is selected from γ-aminopropyltriethoxysilane; Preferably, the second dispersant is selected from ethanol; Preferably, the reducing agent is selected from carboxylic acids; Preferably, the curing agent is selected from polyetheramines.
9. The method for preparing the silver-based transient liquid phase conductive adhesive according to any one of claims 6 to 8, characterized in that: include: Adding the first metal filler and the coupling agent into the second dispersant, stirring and ultrasonically dispersing, to prepare a solution A; Adding the second metal filler and the reducing agent into the second dispersant and performing ultrasonic dispersion to prepare a solution B; The solution A and the solution B are mixed, stirred and ultrasonicated for 20 to 40 minutes to obtain a mixed solution; The polymer matrix is heated and maintained at 50-70° C. for 4-6 minutes, the mixed solution is added, and stirring is continued for 50-70 minutes, and a curing agent is added to obtain a paste-like conductive adhesive with viscosity.
10. Use of the silver-based transient liquid phase conductive adhesive according to any one of claims 6 to 8 or the silver-based transient liquid phase conductive adhesive prepared by the preparation method according to claim 9 in automotive electronics, power electronics or aerospace.